LAND MARKET – THE MECHANISM OF EFFICIENT USE - Shpik, Н.; Smoliarchuk, М. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
The work highlights the role of the land market in Ukraine with all its positive and negative characteristics. The authors proposed a scheme of land relations development from land use to land ownership, where the basis of market relations is made by private property with the appropriate regulatory and legal framework. One has analyzed the main economic mechanisms of land use regulation, which will provide a perfect legal regulation of the land market with the arranged lease relations under the proper inventory of property rights. It is proposed to regulate pricing by introducing an affordable system of taxation and strict liability for violations of the legislation in the field of market relations. The article outlines the key functions of the land market, which reveal the market infrastructure – from land distribution and its transfer to the use of new technologies, the formation of an affordable price for the land plot, taking into account supply and demand, and control over agricultural land use. The research describes stages of peasant farms development, which play an important role in evolution of the land market. The work reveals several reasons affecting the land market, mainly: lack of efficient land use, changes in qualitative and quantitative accounting of lands, changes in natural soil properties (humus content, physical clay content and depth of humus horizon), and erosion processes causing a large amount of nutrients is washed from the soil. A particular attention is paid to the issue of land monitoring, without which the land market and related market relations will be imperfect. It is necessary to develop a system of measures that would promote the efficient use of land to achieve an efficient market. The authors carried out an analysis of the existing experience of the land market in European countries, where each country has its land market system with the appropriate legal framework.